Pengaruh Label Halal, Kesadaran Halal dan Bahan Makanan Terhadap Minat Beli Makanan Kuliner di Pekanbaru - Endrianto Ustha (Al-Manar Journal of Accountancy and Business Studies, 2026)
This study aims to determine the effect of halal labels, halal awareness, and food ingredients on culinary purchase intention in Pekanbaru. The study population was all Muslim food lovers in Pekanbaru. A sample size of 112 was obtained by multiplying the number of indicators by 10. Instrument testing was conducted using validity and reliability tests. Multiple linear regression analysis was used to determine the effect of the independent variables on the dependent variable. The results showed that halal awareness and food ingredients influenced culinary purchase intention in Pekanbaru. However, halal labels did not influence culinary purchase intention in Pekanbaru, meaning that even without halal labels, respondents still purchased culinary products in Pekanbaru.